FORENSIC ASPECTS OF CIRCULATORY DISORDERS IN BRAIN INJURIES - Jumanazarovich, Jarimbetov Rashid (Journal of Medical Genetics and Clinical Biology, 2024)
General Background: The analysis of forensic medical reports reveals persistent challenges in accurately identifying and assessing craniocerebral injuries. Specific Background: Repeated and additional forensic examinations often highlight shortcomings and errors attributed to a lack of understanding among experts regarding contemporary concepts related to traumatic brain injury (TBI), including its mechanisms, clinical manifestations, and differential diagnosis. Knowledge Gap: Despite advancements in medical knowledge, there remains a significant gap in the expertise of forensic professionals regarding the complexities of TBI, leading to inconsistencies in forensic assessments. Aims: This study aims to evaluate the current practices in forensic medical examinations of craniocerebral injuries and identify areas for improvement in the methodology of assessment. Results: The findings indicate that insufficient knowledge of TBI mechanisms and a lack of standardized approaches contribute to errors in forensic evaluations, ultimately affecting the quality of forensic medical reports. Novelty: This research emphasizes the need for enhanced training and a unified methodological framework for forensic experts to better understand and assess craniocerebral injuries. Implications: By addressing these deficiencies, the study underscores the importance of improving forensic practices, which could lead to more accurate diagnoses and assessments of TBI, thereby enhancing the reliability of forensic medical reports in legal contexts. This work advocates for the development of standardized guidelines and continuous education for forensic experts in the field.